Synthesis method of titanium dioxide / graphite phase carbon nitride bimetallic monatomic supported catalyst
By preparing bimetallic single-atom catalysts on titanium dioxide/graphite phase carbon nitride composite materials, the problems of insufficient catalyst preparation complexity and stability in the prior art are solved, and efficient and stable photocatalytic water decomposition effect is achieved.
Patent Information
- Application Number
- CN202411258772.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-07
AI Technical Summary
The existing single-atom metal-supported catalysts are complex in preparation, the products are not easy to separate, the catalytic efficiency is low, the selectivity is poor and the stability is insufficient, making it difficult to meet the long-term catalytic requirements.
The preparation method of titanium dioxide/graphite phase carbon nitride composite supported bimetallic catalyst is prepared by creating surface defects on titanium dioxide nanotubes and graphite phase carbon nitride, combined with sintering method and deposition precipitation method, and a single-atom composite catalyst is prepared to achieve platinum and uniform loading of copper bimetallic nanoparticles.
Bimetallic catalysts with high catalytic activity, high stability and easy recovery are obtained, which are suitable for large-scale industrial applications, significantly improving the efficiency and selectivity of photocatalytic water decomposition.
Smart Images

Figure CN119259094A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for synthesizing a titanium dioxide / graphite phase carbon nitride bimetallic single atom supported catalyst, belonging to the technical field of chemical catalysts. Background Art
[0002] Single-atom catalysts are considered to be the most efficient catalysts, and their uniqueness lies in the fact that they contain isolated atoms as the active centers of the catalysts. Compared with doping of nanoclusters, nanoparticles and bulk materials: single-atom catalysts have unique electronic structures and unsaturated coordination sites, which give them excellent catalytic activity and selectivity; the maximization of atomic utilization greatly reduces costs.
[0003] In recent years, researchers have widely applied single-atom loading. Han et al. demonstrated that single-atom sites played a major role in the hydrogenation of 3-nitrostyrene (Angewandte Chemie International Edition, 2020, 59(29):11824-11829); Chen et al. synthesized a single-atom Pt-loaded anatase TiO2 catalyst (Pt1δ+ / TiO2) by electrostatic ion exchange and spatial closure strategy (Journal of the American Chemical Society, 2018, 140(24):7407-7410). Therefore, the construction of single-atom catalysts can improve the material energy band and electronic structure and affect the material's light absorption performance and carrier transfer kinetics, thereby affecting the photocatalytic process, showing great potential in promoting the development of photocatalytic applications.
[0004] However, the above studies all focus on single supported metal catalysts and common deposited metal particles. Most of the single-atom metal supported catalysts reported in the prior art are single-support single-metal, and the method and process are complicated and the product is not easy to separate. In addition, the catalysts prepared in the prior art have low catalytic efficiency, poor selectivity, easy to change morphology, and most importantly, poor stability during the catalytic reaction, making it difficult to meet the long-term catalytic requirements. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention proposes a method for preparing a titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst. The catalyst prepared by the present invention has a clearly visible single-atom morphology, a quantitatively controllable component composition, high catalytic activity, high stability, is non-toxic and harmless, and is easy to recycle and reuse. This method is suitable for large-scale industrial applications.
[0006] The main technical solution of the present invention is to firstly introduce reducing gas into titanium dioxide nanotubes and graphite carbon nitride to respectively create surface defects, then prepare titanium dioxide / graphite carbon nitride composite catalyst by sintering method, then deposit Pt-Cu bimetallic nanoparticles on the surface of the composite catalyst by deposition precipitation method to obtain single atom composite catalyst, and finally prepare the catalyst by filtering and washing. The specific implementation process is as follows: A method for preparing a titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst comprises the following steps: (1) Titanium dioxide p25 is uniformly dispersed in a sodium hydroxide solution with a molar concentration of 8-12M, and the mass volume ratio of titanium dioxide to sodium hydroxide solution is (1-10): 400g / ml. The reaction is carried out in a closed reactor at 120-160°C. The product is ion-exchanged with a hydrochloric acid solution with a molar concentration of 0.05-0.2M, and then calcined in an air atmosphere at 300-500°C to obtain titanium dioxide nanotubes. (2) calcining the titanium dioxide nanotubes prepared in step (1) at 150-300° C. in a hydrogen-argon mixed gas atmosphere to obtain nanotubes with oxygen vacancy defects; (3) After fully mixing ammonium chloride and melamine in a mass ratio of 4:1 to 8:1, calcining at 450 to 550°C for 3 to 5 hours, 2D flake graphite phase carbon nitride can be obtained; (4) adding the graphite phase carbon nitride powder obtained in step (3) to a 0.5-2 mol / L HCl solution, subjecting the sample to a hydrothermal reaction at 120-170°C for 3-5 h, centrifugally washing the sample, adding the sample to 0.5-2 M ammonia water for ultrasonic treatment, centrifugally separating the sample, and washing the sample with deionized water until the pH value is 6-7; drying the sample, calcining the sample at 450-550°C for 1-2 h in a hydrogen-argon mixed gas atmosphere, and cooling the sample to obtain the sample; (5) taking the oxygen vacancy defect titanium dioxide sample obtained in step (2) and the carbon defect graphite phase carbon nitride obtained in step (4), mixing them together, and grinding and mixing them uniformly; then calcining the mixture at 250-400° C. in a nitrogen atmosphere for 1-2 h; after cooling the sample to room temperature, obtaining a light yellow powder; (6) The defective titanium dioxide / graphite phase carbon nitride obtained in step (5) is dispersed in anhydrous ethanol, and then 0.5-2M ammonium carbonate solution is added dropwise until the pH value is 8-9, and then 0.5-1mM chloroplatinic acid and 20-30mM copper chloride solution are added dropwise so that the mass ratio of platinum ions to defective titanium dioxide / graphite phase carbon nitride is 0.003-0.006:1, and the mass fraction ratio of copper ions to defective titanium dioxide / graphite phase carbon nitride is 0.0005-0.002:1. Finally, the product is centrifuged and washed, and then calcined at 150-250°C in a hydrogen-argon mixed gas atmosphere for 1-2h to obtain a bimetallic single atom-supported titanium dioxide / graphite phase carbon nitride composite catalyst.
[0007] In the above step (1), the mass volume ratio of titanium dioxide to sodium hydroxide solution is 1:60 g / ml.
[0008] In the above step (1), the hydrothermal reaction time is 16-32 hours, and the calcination temperature is 400°C.
[0009] In the above steps (2), (4) and (6), the volume ratio of hydrogen to argon in the hydrogen-argon mixed gas is H2:Ar=1:8~1:9.5.
[0010] In the above step (3), the muffle furnace calcination temperature and time is 4 hours.
[0011] In the above step (5), the mass ratio of titanium dioxide to graphite phase carbon nitride is 1:1.5.
[0012] In the above step (6), the mass ratio of platinum ions added dropwise with chloroplatinic acid to defective titanium dioxide / graphite phase carbon nitride is 0.004:1.
[0013] In the above step (6), the mass fraction ratio of copper ions added by copper chloride to defective titanium dioxide / graphite phase carbon nitride is 0.001:1.
[0014] Application of the titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst prepared by the above method in photocatalytic water decomposition.
[0015] The present invention has the following advantages: 1. The titanium dioxide nanotube carrier catalyst used in the present invention has better conductivity than titanium dioxide with a microscopic morphology of nanoparticles, and can significantly inhibit the recombination of photogenerated electron-hole pairs; graphite phase carbon nitride has a 2D structure similar to graphene, has good conductivity, and can also inhibit the recombination of photogenerated electron-hole pairs; 2. The present invention constructs vacancy defects on the carrier and uses a deposition precipitation method to prepare a titanium dioxide / graphite phase carbon nitride single-atom bimetallic composite catalyst with uniform distribution of single-atom metal deposited particles on the carrier surface, high catalytic activity and high stability; 3. The present invention has a high catalytic effect at a lower loading amount through the method of co-loading single atoms of metals and precious metals, and compared with the general double precious metal or non-precious metal single atom deposition, it reduces the cost and has more efficient catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Scanning electron microscope (SEM) photo of the titanium dioxide nanotube catalyst prepared in Example; Figure 2Scanning electron microscope (SEM) photograph of the graphite phase carbon nitride catalyst prepared in Example; Figure 3 Scanning electron microscope (SEM) photo of the titanium dioxide / graphite phase carbon nitride single atom bimetallic composite catalyst prepared in Example; Figure 4 X-ray photoelectron spectroscopy XPS analysis results of the titanium dioxide / graphite phase carbon nitride single atom bimetallic composite catalyst prepared in Example; Figure 5 Bar graph comparing the catalytic performance of different catalysts prepared by different methods; Figure 6 This is the HAADF-STEM image of the titanium dioxide / graphite phase carbon nitride single atom bimetallic composite catalyst prepared in Example 1. DETAILED DESCRIPTION
[0017] The technical solution of the present invention is further described below in conjunction with the examples and the accompanying drawings, but the scope of protection of the present invention is not limited thereto. The titanium dioxide described in the examples was purchased from Degussa, Germany. Example 1
[0018] A method for preparing a titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst comprises the following steps: (1) 1.0 g of titanium dioxide p25 was evenly dispersed in 60 ml of a 10 M sodium hydroxide solution, stirred for 3 h, and then ultrasonicated for 0.5 h before being transferred to a reactor and reacted in a constant temperature drying oven at 140 ° C for 24 h. After the obtained product was cooled to room temperature, ion exchange was performed in a 0.1 M hydrochloric acid solution, and then calcined in a muffle furnace at 400 ° C for 2 h to obtain a titanium dioxide nanotube sample.
[0019] (2) The titanium dioxide nanotubes prepared in step (1) were placed in a tubular furnace in a hydrogen-argon mixed gas (H2=10%) atmosphere and calcined at 200°C for 2 h to obtain nanotubes with oxygen vacancy defects.
[0020] (3) Take 6 g of ammonium chloride and 1 g of melamine and mix them thoroughly. Put them into a crucible and calcine them at 500 °C in a muffle furnace for 4 hours to obtain 2D flake graphite phase carbon nitride.
[0021] (4) The graphite phase carbon nitride powder obtained in step (3) was placed in 40 mL of 1M HCl solution, stirred for 30 min, transferred to a reactor, and hydrothermally reacted at 150°C in a constant temperature drying oven for 4 h, and cooled to room temperature. Most of the acid and some large crystalline particles in the reactor were removed, and then the sample was centrifuged. After centrifugation, the sample was placed in 1M ammonia water, ultrasonicated for 30 min, centrifuged, and washed with deionized water until the pH was 6-7. The sample was placed in an oven at 80°C for 10 h, and then a certain amount of the sample was placed in a porcelain ark. Finally, the porcelain ark was placed in a tube furnace and calcined at 500°C for 1 h in a hydrogen-argon mixture (H2=10%), and cooled to obtain the sample.
[0022] (5) Take 0.6 g of the oxygen vacancy defect titanium dioxide sample prepared in (2) and 0.4 g of the carbon defect graphite phase carbon nitride prepared in (4), and grind and mix them evenly in an agate mortar. Then spread the mixture evenly in a square porcelain boat, place it in a tube furnace, and calcine it at 300°C in a nitrogen atmosphere for 2 h. After the sample is cooled to room temperature, a light yellow powder is obtained.
[0023] (6) Take 0.1 g of the defective titanium dioxide / graphite phase carbon nitride obtained in (5) and dissolve it in 50 mL of anhydrous ethanol, and ultrasonically disperse it for 30 min. Then, add 7 ml of 1 M ammonium carbonate solution dropwise while stirring to adjust the pH value to about 8.5, then add 265 μl of 7.72 mM chloroplatinic acid solution and 65 μl of 23.9 mM copper chloride solution, and continue stirring for 6 h. Finally, centrifuge and wash the product, place it in a tubular furnace, and calcine it at 200 ° C for 2 h in a hydrogen-argon mixed gas (H2 = 10%) atmosphere to obtain a bimetallic single atom-supported titanium dioxide / graphite phase carbon nitride composite catalyst.
[0024] The bimetallic single-atom-loaded titanium dioxide / graphite-phase carbon nitride composite catalyst prepared by the above method is composed of titanium dioxide nanotubes and graphite-phase carbon nitride as carriers, and platinum and copper single-atom particles are uniformly loaded on the carrier surface; wherein the titanium dioxide nanotube has a diameter of about 20nm, a uniform tube diameter, and a length of about 5-10μm; the graphite-phase carbon nitride sheet structure is uniformly dispersed, the surface is stretched, and the thickness is only about 5nm, providing more anchoring points for single metal loading; the bimetallic particle size is 1-2nm, the particle spacing is 5-10nm, the particles are uniformly loaded on the carrier surface, there is no large area of blank and a large amount of agglomeration phenomenon, and the theoretical mass fraction is (SACs) 0.4%Pt / 0.1%Cu.
[0025] The SEM images of the titanium dioxide nanotubes, graphite carbon nitride and bimetallic single atom-supported titanium dioxide / graphite carbon nitride composite catalyst are shown in the attached Figures 1 to 3 , X-ray photoelectron spectroscopy (XPS) analysis results are shown in Figure 4 The results showed that the catalyst contained platinum and copper elements. Example 2
[0026] A method for preparing a titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst comprises the following steps: (1) 1.0 g of titanium dioxide p25 was evenly dispersed in 50 ml of a 12 M sodium hydroxide solution, stirred for 3 h, and then ultrasonicated for 0.5 h before being transferred to a reactor and reacted in a constant temperature drying oven at 130 ° C for 30 h. After the obtained product was cooled to room temperature, ion exchange was performed in a 0.1 M hydrochloric acid solution, and then calcined in a muffle furnace at 500 ° C for 1 h to obtain a titanium dioxide nanotube sample.
[0027] (2) The titanium dioxide nanotubes prepared in step (1) were placed in a tubular furnace in a hydrogen-argon mixed gas (H2=10%) atmosphere and calcined at 200°C for 2 h to obtain nanotubes with oxygen vacancy defects.
[0028] (3) Take 6 g of ammonium chloride and 1 g of melamine and mix them thoroughly. Put them into a crucible and calcine them at 500 °C in a muffle furnace for 3 hours to obtain 2D flake graphite phase carbon nitride.
[0029] (4) Place the graphite phase carbon nitride powder obtained in step (3) in 30 mL of 2M HCl solution and stir for 30 min. , Transfer the reactor, perform hydrothermal reaction at 150°C in a constant temperature drying oven for 4 hours, and cool to room temperature. Remove most of the acid and some large crystalline particles in the reactor, and then centrifuge the sample. After centrifugation, place the sample in 1M ammonia water, ultrasonicate for 30 minutes, centrifuge, and wash the sample with deionized water until the pH is 6-7. Dry the sample in an oven at 80°C for 10 hours, then place a certain amount of the sample in a porcelain ark, and finally place the porcelain ark in a tubular furnace, calcine at 500°C for 1 hour under a hydrogen-argon mixture (H2=10%), and cool to obtain the sample.
[0030] (5) Take 0.5 g of the oxygen vacancy defect titanium dioxide sample prepared in (2) and 0.5 g of the carbon defect graphite phase carbon nitride prepared in (4), and mix them together, and grind them thoroughly in an agate mortar until they are evenly mixed. Then spread the mixture evenly in a square porcelain boat, place it in a tube furnace, and calcine it at 300°C in a nitrogen atmosphere for 2 h. After the sample is cooled to room temperature, a light yellow powder is obtained.
[0031] (6) Take 0.1 g of the defective titanium dioxide / graphite phase carbon nitride obtained in (5) and dissolve it in 50 mL of anhydrous ethanol, and ultrasonically disperse it for 30 min. Then, add 7 ml of 1 M ammonium carbonate solution dropwise while stirring to adjust the pH value to about 8.5, then add 335 μl of 7.72 mM chloroplatinic acid solution and 65 μl of 23.9 mM copper chloride solution, and continue stirring for 6 h. Finally, centrifuge and wash the product, place it in a tubular furnace, and calcine it at 200 ° C for 2 h in a hydrogen-argon mixed gas (H2=10%) atmosphere to obtain a bimetallic single atom-supported titanium dioxide / graphite phase carbon nitride composite catalyst.
[0032] The bimetallic single-atom-loaded titanium dioxide / graphite-phase carbon nitride composite catalyst prepared by the above method is composed of titanium dioxide nanotubes and graphite-phase carbon nitride as carriers, and platinum and copper single-atom particles are uniformly loaded on the carrier surface; wherein the titanium dioxide nanotube has a diameter of about 20nm, a uniform tube diameter, and a length of about 5-10μm; the graphite-phase carbon nitride flaky structure is uniformly dispersed, the surface is stretched, and the thickness is only about 5nm, providing more anchoring points for single metal loading; the bimetallic particle size is 1-2nm, the particle spacing is 5-10nm, the particles are uniformly loaded on the carrier surface, there is no large area of blank and a large amount of agglomeration phenomenon, and the theoretical mass fraction is (SACs) 0.5%Pt / 0.1%Cu. Example 3
[0033] A method for preparing a titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst comprises the following steps: (1) 1.0 g of titanium dioxide p25 was evenly dispersed in 60 ml of 8 M sodium hydroxide solution, stirred for 3 h, and then ultrasonicated for 0.5 h before being transferred to a reactor and reacted in a constant temperature drying oven at 150 ° C for 20 h. After the obtained product was cooled to room temperature, ion exchange was carried out in a 0.1 M hydrochloric acid solution, and then calcined in a muffle furnace at 300 ° C for 3 h to obtain a titanium dioxide nanotube sample.
[0034] (2) The titanium dioxide nanotubes prepared in step (1) were placed in a tubular furnace in a hydrogen-argon mixed gas (H2=10%) atmosphere and calcined at 200°C for 2 h to obtain nanotubes with oxygen vacancy defects.
[0035] (3) Take 6 g of ammonium chloride and 1 g of melamine and mix them thoroughly. Put them into a crucible and calcine them in a muffle furnace at 500 °C for 5 hours to obtain 2D flake graphite phase carbon nitride.
[0036] (4) The graphite phase carbon nitride powder obtained in step (3) was placed in 50 mL of 0.5 M HCl solution, stirred for 30 min, transferred to a reactor, and hydrothermally reacted at 150 ° C in a constant temperature drying oven for 4 h, and cooled to room temperature. Most of the acid and some large crystalline particles in the reactor were removed, and then the sample was centrifuged. After centrifugation, the sample was placed in 1 M ammonia water, ultrasonicated for 30 min, centrifuged, and washed with deionized water until the pH was 6-7. The sample was placed in an oven at 80 ° C for 10 h, and then a certain amount of the sample was placed in a porcelain ark. Finally, the porcelain ark was placed in a tubular furnace and calcined at 500 ° C for 1 h in a hydrogen-argon mixture (H2 = 10%), and cooled to obtain the sample.
[0037] (5) Take 0.7 g of the oxygen vacancy defect titanium dioxide sample prepared in (2) and 0.3 g of the carbon defect graphite phase carbon nitride prepared in (4), and mix them together, and grind and mix them evenly in an agate mortar. Then spread the mixture evenly in a square porcelain boat, place it in a tube furnace, and calcine it at 300°C in a nitrogen atmosphere for 2 h. After the sample is cooled to room temperature, a light yellow powder is obtained.
[0038] (6) Take 0.1 g of the defective titanium dioxide / graphite phase carbon nitride obtained in (5) and dissolve it in 50 mL of anhydrous ethanol, and ultrasonically disperse it for 30 min. Then, add 7 ml of 1 M ammonium carbonate solution dropwise while stirring to adjust the pH value to about 8.5, then add 200 μl of 7.72 mM chloroplatinic acid solution and 135 μl of 23.9 mM copper chloride solution, and continue stirring for 6 h. Finally, centrifuge and wash the product, place it in a tubular furnace, and calcine it at 200 ° C for 2 h in a hydrogen-argon mixed gas (H2 = 10%) atmosphere to obtain a bimetallic single atom-supported titanium dioxide / graphite phase carbon nitride composite catalyst.
[0039] The bimetallic single-atom-loaded titanium dioxide / graphite-phase carbon nitride composite catalyst prepared by the above method is composed of titanium dioxide nanotubes and graphite-phase carbon nitride as carriers, and platinum and copper single-atom particles are uniformly loaded on the carrier surface; wherein the titanium dioxide nanotube has a diameter of about 20nm, a uniform tube diameter, and a length of about 5-10μm; the graphite-phase carbon nitride flaky structure is uniformly dispersed, the surface is stretched, and the thickness is only about 5nm, providing more anchoring points for single metal loading; the bimetallic particle size is 1-2nm, the particle spacing is 5-10nm, the particles are uniformly loaded on the carrier surface, there is no large area of blank and a large amount of agglomeration phenomenon, and the theoretical mass fraction is (SACs) 0.3%Pt / 0.2%Cu.
[0040] Example 4 Catalyst performance test, the test method is as follows: The device used for the photocatalytic hydrogen production reaction is the Beijing Perfek Labsolar-Ⅲ AG online analysis system, which is equipped with a Beifen 3410A gas chromatograph. First, weigh 50 mg of the catalyst and put it into the reaction vessel, add 90 mL of deionized water and 10 mL of sacrificial agent, and stir it magnetically. The temperature of the circulating condensed water is set to 10 ° C, the reaction vessel is sealed, and the device is evacuated with a vacuum pump, and N2 is introduced as the carrier gas. A 300W xenon lamp is used as the reaction light source. The xenon lamp is kept 10 cm away from the liquid surface, and the amount of hydrogen generated is detected every 1 hour. The detection conditions of the gas chromatography are: column box temperature 80 ° C, injection port temperature 100 ° C, TCD detector temperature 100 ° C, and carrier gas is N2. The internal standard method is used for chromatographic detection of hydrogen.
[0041] The catalytic results are shown in the attached Figure 5 The attached figure is a comparison of the catalytic performance of different catalysts prepared by different methods, which are graphite carbon nitride (CN), titanium dioxide nanotubes (TNT), defective titanium dioxide nanotubes / defective graphite carbon nitride (0.6 / 0.4) (VCN / VTNT) and loaded single metal platinum (0.4Pt-VCN / VTNT), copper (0.1Cu-VCN / VTNT) and loaded bimetallic (0.4Pt0.1Cu-VCN / VTNT) catalysts for photocatalytic hydrogen production performance comparison.
[0042] Depend on Figure 5 The data shows that the photocatalytic hydrogen production effect of the bimetallic single atom-loaded titanium dioxide / graphite phase carbon nitride composite catalyst is the best, reaching 3735.2μmol / g·h, which is 153 times higher than the performance of pure titanium dioxide nanotubes. The photocatalytic hydrogen production effect of the bimetallic platinum-copper copper also achieves a higher catalytic effect than that of the monometallic platinum.
Claims
1. A method for preparing a titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst, characterized in that The following steps are involved: (1) Titanium dioxide p25 is uniformly dispersed in a sodium hydroxide solution with a molar concentration of 8-12M, and the mass volume ratio of titanium dioxide to sodium hydroxide solution is (1-10): 400g / ml. The reaction is carried out in a closed reactor at 120-160°C. The product is ion-exchanged with a hydrochloric acid solution with a molar concentration of 0.05-0.2M, and then calcined in an air atmosphere at 300-500°C to obtain titanium dioxide nanotubes. (2) calcining the titanium dioxide nanotubes prepared in step (1) at 150-300° C. in a hydrogen-argon mixed gas atmosphere to obtain nanotubes with oxygen vacancy defects; (3) After fully mixing ammonium chloride and melamine in a mass ratio of 4:1 to 8:1, calcining at 450 to 550°C for 3 to 5 hours, 2D flake graphite phase carbon nitride can be obtained; (4) adding the graphite phase carbon nitride powder obtained in step (3) to a 0.5-2 mol / L HCl solution, subjecting the sample to a hydrothermal reaction at 120-170°C for 3-5 h, centrifugally washing the sample, adding the sample to 0.5-2 M ammonia water for ultrasonic treatment, centrifugally separating the sample, and washing the sample with deionized water until the pH value is 6-7; drying the sample, calcining the sample at 450-550°C for 1-2 h in a hydrogen-argon mixed gas atmosphere, and cooling the sample to obtain the sample; (5) taking the oxygen vacancy defect titanium dioxide sample obtained in step (2) and the carbon defect graphite phase carbon nitride obtained in step (4), mixing them together, and grinding and mixing them uniformly; then calcining the mixture at 250-400° C. in a nitrogen atmosphere for 1-2 h; after cooling the sample to room temperature, obtaining a light yellow powder; (6) The defective titanium dioxide / graphite phase carbon nitride obtained in step (5) is dispersed in anhydrous ethanol, and then 0.5-2M ammonium carbonate solution is added dropwise until the pH value is 8-9, and then 0.5-1mM chloroplatinic acid and 20-30mM copper chloride solution are added dropwise so that the mass ratio of platinum ions to defective titanium dioxide / graphite phase carbon nitride is 0.003-0.006:1, and the mass fraction ratio of copper ions to defective titanium dioxide / graphite phase carbon nitride is 0.0005-0.002:
1. Finally, the product is centrifuged and washed, and then calcined at 150-250°C in a hydrogen-argon mixed gas atmosphere for 1-2h to obtain a bimetallic single atom-supported titanium dioxide / graphite phase carbon nitride composite catalyst.
2. The method for preparing the titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst according to claim 1, characterized in that: In the above step (1), the mass volume ratio of titanium dioxide to sodium hydroxide solution is 1:60 g / ml.
3. The method for preparing the titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst according to claim 1, characterized in that: In the above step (1), the hydrothermal reaction time is 16 to 32 hours, and the calcination temperature time is 400° C. for 2 hours.
4. The method for preparing the titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst according to claim 1, characterized in that: In the above steps (2), (4) and (6), the volume ratio of hydrogen to argon in the hydrogen-argon mixed gas is H2:Ar=1:8~1:9.
5.
5. The method for preparing the titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst according to claim 1, characterized in that: In the above step (5), the mass ratio of titanium dioxide to graphite phase carbon nitride is 1:1-2.
6. The method for preparing the titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst according to claim 1, characterized in that: In the above step (6), the mass ratio of platinum ions added dropwise with chloroplatinic acid to defective titanium dioxide / graphite phase carbon nitride is 0.004:
1.
7. The method for preparing the titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst according to claim 1, characterized in that: In the above step (6), the mass fraction ratio of copper ions of the added copper chloride to the defective titanium dioxide / graphite phase carbon nitride is 0.001:
1.
8. The titanium dioxide / graphite phase carbon nitride composite supported bimetallic catalyst prepared by the method of claim 1.
9. Use of the titanium dioxide / graphite-phase carbon nitride composite supported bimetallic catalyst according to claim 8 in photocatalytic water decomposition.